Evaluation of mineralized collagen and α-tricalcium phosphate as scaffolds for tissue engineering of bone using human mesenchymal stem cells - Niemeyer, Philipp; Krause, Ulf; Fellenberg, Jörg; Kasten, Philip; Seckinger, Anja; Ho, Anthony Dick; Simank, Hans-Georg (Cells tissues organs, 2004)
Owing to their plasticity and high proliferation capacity in vitro, mesenchymal stem cells (MSC) isolated from human bone marrow are promising candidates for use in tissue engineering approaches for the repair or replacement of mesenchymal tissues such as bone, cartilage or tendon. In keeping with the tissue engineering concept, these cells are cultivated on three-dimensional (3D) scaffolds to replace 3D tissue defects. Among the scaffolds tested for tissue engineering of bone, those containing phosphorus and calcium, as natural bone does, are the most promising candidates for this purpose. In this study, MSC from five patients were isolated from bone marrow. After in vitro expansion, cells were cultivated and differentiated towards the osteogenic lineage on mineralized collagen sponges and α-tricalcium phosphate (α-TCP). To analyze how appropriate these scaffolds would be for tissue engineering purposes, we established an in vitro characterization system to describe seeding efficiency, cell distribution and proliferation behavior on each scaffold. Real-time reverse transcriptase polymerase chain reaction quantification of important genes involved in osteogenic differentiation [e.g. bone sialoprotein (BSP), bone morphogenic protein 2, alkaline phosphatase and osteocalcin] was used to monitor the differentiation process of cells seeded on mineralized collagen and α-TCP. Using this in vitro characterization, we were able to demonstrate effective 3D growth of MSC on both scaffolds investigated. Improved osteogenic differentiation was observed on the scaffolds as compared to control monolayers. Of the two matrices, mineralized collagen was superior to α-TCP with regard to seeding efficacy (98 vs. 67%, p = 0.0003), increase in osteogenic marker genes (BSP expression on day 24, pcollagen vs. TCP = 0.046) and 3D cell alignment (cell infiltration up to 500 vs. 200 µm). In conclusion, our data suggest that mineralized collagen is a promising candidate for use as a scaffold in tissue engineering of bone.
Gesehen am 03.12.2021